PENGARUH DISIPLIN KERJA, KOMPETENSI DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA CV GAVRA PERKASA GRESIK - jurnalpps pps; Diah Vivi Astriyani; Woro Utari; Cathrine Sri Hartati (Jurnal Manajerial Bisnis, 2019)
ABSTRACT The aims of this research were to describe about job discipline, competence and incentive to work performance of CV Gavra Perkasa Gresik; to analyze the effect of job discipline, competence and incentive partially to work performance of CV Gavra Perkasa Gresik; to analyze the effect of job discipline, competence and incentive simultaneously to work performance of CV Gavra Perkasa Gresik. The kind of this research is categorized as explanatory research and using quantitative research approach. The populations of this research were all employers of CV Gavra Perkasa Gresik. the sampling technique of this research by using census sampling. So, sample of this research were 100 people. From the result of this research can be concluded that the conditions of job discipline, competence, incentive and work performance of CV Gavra Perkasa Gresik in very good category. Job discipline, competence and incentive partially have significant effect to work performance of CV Gavra Perkasa Gresik. Job discipline, competence and incentive simultaneously have significant effect to work performance of CV Gavra Perkasa Gresik. Keywords : job discipline, competence, incentive and work performance